Does corporate governance reduce overinvestment? The mediating role of information asymmetry - Samya Tahir; Muhammad Ali Jibran Qamar; Mian Sajid Nazir; Muhammad Usman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study investigates the direct and indirect relationship between corporate governance and agency cost using bootstrap analysis. For a sample of 155 firms during 2009-2015, this study finds statistically significant both direct effect of corporate governance on agency cost of overinvestment, and an indirect effect mediated by information asymmetry, with favoring the indirect effect as more important in reducing agency cost. The direct effect shows that despite increasing corporate governance mechanism, the agency cost of overinvestment is rising. However, the indirect effect suggests that the corporate governance mechanism promotes transparency by exerting pressure on management to produce information that investors and other stakeholders can use. This creates a monitoring channel that reduces information asymmetry, thus reducing the ability of management and majority shareholders to expropriate the firm's resources that mitigates overinvestment of free cash flow. The results provide implications for regulators that theeffectiveness of corporate governance practices should be watched carefullyto reduce managerial opportunism and controlling shareholders' expropriation in firms. Moreover, the regulatory authorities should collaborate with firms' management to frame disclosure policies that investors can use as a monitoring device to make firmsunable to overinvest free cash flow.
Keywords: 330; corporate governance index; information asymmetry; agency cost; Bootstrapping analysis